PROBLEMS OF TRAINING OF MILITARY TRANSLATORS (Web of Technology: Multidimensional Research Journal, 2026)
The role of a military translator or interpreter is one of the most intellectually demanding and high-stakes professions in the linguistic world. Unlike general translation, where the consequences of a nuance lost might result in mild confusion or a minor business loss, military translation operates in an environment where linguistic precision is directly tied to operational safety, intelligence accuracy, and the preservation of human life. As international military cooperation and peacekeeping missions expand, the need for highly skilled linguistic mediators becomes paramount. However, the current landscape of training military translators faces significant structural, cognitive, and pragmatic hurdles. Addressing these challenges requires a shift from traditional pedagogical models toward a more holistic, technology-integrated, and psychologically resilient training framework.